2008
DOI: 10.1097/ta.0b013e318161b0ab
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Plasma Glucose and Glycosylated Hemoglobin A1C Levels Among Nondiabetic Trauma Patients

Abstract: : Almost a quarter of nondiabetic trauma patients presenting with hyperglycemia were found to have elevated gHbA1C levels and ODM. Risk factors for ODM included advancing age and body mass index as well as being Native American. The hyperglycemia seen in trauma patients should not solely be attributed to the hormonal and metabolic response to injury; wider ODM screening for both acute management strategies and long-term health benefits is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…Finally, the purpose of our investigation was to evaluate hyperglycemia in orthopaedic trauma patients without a history of diabetes. While authors of previous studies have commented that patients with stress-hyperglycemia may include both undiagnosed diabetics and nondiabetics 17,23 , a recent prospective study demonstrated that nearly 5% of general trauma patients were diagnosed with occult diabetes mellitus on the basis of hemoglobin A1C blood values 27 . Such laboratory values were not routinely collected at our institution, and therefore patients with occult diabetes could not be identified from this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the purpose of our investigation was to evaluate hyperglycemia in orthopaedic trauma patients without a history of diabetes. While authors of previous studies have commented that patients with stress-hyperglycemia may include both undiagnosed diabetics and nondiabetics 17,23 , a recent prospective study demonstrated that nearly 5% of general trauma patients were diagnosed with occult diabetes mellitus on the basis of hemoglobin A1C blood values 27 . Such laboratory values were not routinely collected at our institution, and therefore patients with occult diabetes could not be identified from this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of counterregulatory hormones and cytokines leads to failure of insulin to suppress hepatic gluconeogenesis in a hyperglycemic environment [15]. Many studies have been done to demonstrate the significant portions of hospitalized patients exhibiting hyperglycemia, many of whom meet the criteria for diabetes, with no history of a previous diagnosis of the disease [16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…2 Levetan et al 4 followed over 1000 consecutive adult patients and found an overall 13% incidence of hyperglycemia and a 33% incidence of hyperglycemia in surgical patients who presented without the diagnosis of diabetes. Kopelman et al 5 found an 18% incidence of hyperglycemia in their population of over 1000 nondiabetic trauma patients.…”
Section: Introductionmentioning
confidence: 98%